Is Scale-Appropriate Farm Mechanization Gendered? Learning from the Nepal Hills - Gartaula, Hom Nath; Singh, Madhulika; Paudel, Gokul Prasad (Springer, 2023)
Scale-appropriate farm mechanization could be an important pathway to the UN’s sustainable development goals (SDGs) of attaining gender equality (SDG5) in agriculture. Gender and farm mechanization is getting attention in the academic and public policy domain as a solution to labor scarcity in the smallholder farming systems, which in recent years, is facing challenges of labor shortage due to male labor outmigration. Taking a case study from a maize-based farming system in Nepal hill, this paper illustrates how the promotion of scale-appropriate farm mechanization can be gendered. Using the household survey data collected from the mid-hills of Nepal from 179 mini-tiller adopter farmers, this paper reports that only 4% of the owners were women, and only 1% of women were involved in mini-tiller operations. We find that mini-tiller adopting male and female household head’s maize productivity, profitability, and production costs are similar. The paper concludes by identifying social perception against women, rugged topography, women’s low level of knowledge in operating machines, spare parts maintenance, and added responsibilities resulting in women’s lower participation in mini-tiller adoption decisions. This chapter suggests measures like awareness raising, increasing access, and training built around tailoring women’s needs to reduce the gender gap in farm mechanization.